Analysis of the Development Needs of E-Book Story Media 'BUCETAR' (Picture Story Books) for Elementary School Students in Indonesian Schools Riyadh - Rohmah, Fita Nur; Istiq'faroh, Nurul; Subrata, Heru (Papanda Publisher, 2025)
This study aims to analyze the initial needs in the development of e-book story media